Extrinsic mechanical size effects in thin ZrNi metallic glass films. (15th May 2015) - Ghidelli, M.; Gravier, S.; Blandin, J.-J.; Djemia, P.; Mompiou, F.; Abadias, G.; Raskin, J.-P.; Pardoen, T.
Abstract: Mechanical size effects in Zr x Ni100− x thin metallic glass films are investigated for thicknesses from 200 to 900 nm. Local order, elastic properties and rate sensitivity are shown to be thickness independent, while hardness and fracture resistance are not. The increase of hardness with decreasing thickness is related to the substrate constraint on shear banding. Fracture surfaces exhibit a corrugated morphology, except for thickness below 400 nm exhibiting perfectly flat surfaces. The corrugations appear again on the thinnest films when adding a cap layer, indicating that the fracture mechanisms are primarily dominated by the loading configuration and geometry which constrain the plastic zone extension. Increasing the Ni content from 25% to 58% leads to an increase of elastic modulus, Poisson ratio, strength, activation volume, and fracture toughness. These changes can be understood based on the change in thermodynamic fragility and Zr–Ni bonds formation. Zr75 Ni25 composition shows exceptionally large rate sensitivity exponent equal to 0.058. The fracture mechanisms are not modified by composition and the fracture toughness is systematically low due to the confinement of the plastic zone.